Jasnost in določnost predpisov na področju upravnega nadzora - Čebulj, Janez (Dignitas (Ljubljana), 2015)
This article discusses constitutional and constitutional criteria for the use of undefined legal concepts in the process of administrative control. The legislator is often forced to use one or more of undefined concepts in regulating some areas. However, this raises the question, where is the limit to the level of indeterminacy. Because, unlike discretion, which is focused on the conduct of the administrative body, indefinite concepts in the law are focused on the legal definition of the facts or charachteristics of an actual situation, also the question of legal certainty of legal norms' addressee araises as one of the fundamental issues. The essence of the requirements of clarity and precision of the legal norm is that its addressee knows how to act in a given situation. This requirement could be undermined if the contents of the indeterminate legal concept, consequently, also the required conduct of addressee, is defined only by an administrative (supervisory) authority in the procedure of administrative control. This is especially pressing issue in cases where continuation of the process of administrative supervision (and in that context the fact finding) a punitive procedure. In this context, the article analyzes the case of fictitious legaltransactions in tax law.
Keywords: davčno pravo; načelo jasnosti in določnosti; navidezni pravni posel; nedoločeni pravni pojmi; upravni nadzor